Pengaruh Kualitas Layanan Digital Banking Terhadap Kepuasan Nasabah Pada Bank Syariah Indonesia Di Kabupaten Subang - Nurlatifah, Syifa; Juhadi, Juhadi; Damayanti Rusmana, fenny (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Service quality is one of the factors of consumer satisfaction, so service quality is very important for the business world and organizations. Customer satisfaction with banking services brings long-term benefits to the bank and provides a competitive advantage for the bank itself compared to other banks. If customers are consistently satisfied with their bank's services, they are less likely to switch to another service provider or bank. This way, customers are more likely to reuse the service and promote it to others. The aim of this research is to determine "The Influence of Digital Banking Service Quality on Customer Satisfaction at Indonesian Sharia Banks in Subang Regency". This research is a type of quantitative research. The data in this research was collected using a questionnaire from 100 respondents who used digital banking services from sharia banks. This research uses a sampling technique using Purposive Sampling technique. In this research, the data analysis technique used is SPSS version 29 software. The research results show that the quality of digital banking services has a positive and significant effect on customer satisfaction.